OZN in vprašanje Palestine - Šterbenc, Primož (Teorija in praksa, 2016)
The article deals with the activities of the United Nations (UN) regarding the problem of Palestine. On one hand, the UN has coped with the issue as it set up the legal basis for its resolution, established the Palestinian people's right to self-determination, and created an institutional place for membership of the State of Palestine in the UN. However, the UN has been unable to stop the continuing Israeli violations of international law which have considerably reduced the possibility of creating a Palestinian state. This has been the result of the United States of America's consistent pro-Israeli policies in the UN Security Council. In sum, one can argue that the UN's activities have been a great failure. Yet, the General Assembly of the UN is much less responsible for this failure than the UN Security Council.
Keywords: International law; International relations; Mednarodni odnosi; Mednarodno pravo; National self-determination; Organizacija združenih narodov; Palestina; Palestine; pravica do samoodločbe; Samoodločba narodov; Varnostni svet